Odpowiedzialność usługodawcy za udostępnianie w internetowych serwisach społecznościowych treści przestępnych związanych z publicznym propagowaniem faszystowskiego lub innego totalitarnego ustroju państwa według projektu ustawy o ochronie wolności słowa w internetowych serwisach społecznościowych - Kołodziej, Anastazja (Wydawnictwo Uniwersytetu Wrocławskiego, 2021)
Having in mind the Law on the Provision of Electronic Services, the article presents selected issues in the field of strict liability of the service provider in the form of administrative penalties for publishing on social media criminal content or content that is related to it, in the form of praising or exhorting to commit the crime prohibited under Art. 256 of the Penal Code according to the Draft of the Law on the Protection of Freedom of Speech on Social Media. It presents selected issues concerning inaccuracies and imprecise definitions of the notions of service provider, user, and illegal content, especially in the context of content that does not exhaust the features of a prohibited act under Art. 256 of the Penal Code. It describes also the procedure to be followed in the event of the user’s complaint about blocking their content, profile or a complaint about disseminating illegal content. The author concludes that the assessment of illegal content that does not exhaust the features of a crime under Art. 256 of the Penal Code, but is related to it, in the form of praising or exhorting to commit it, will belong to the Freedom of Speech Committee. Additionally, the regulations of the Law on the Provision of Electronic Services and the Draft of the Law on the Protection of Freedom of Speech on Social Media are inconsistent because, on one hand, after the so-called flagging of the content on social media, the service provider is obliged to remove illegal content (Art. 14 of the Law on the Provision of Electronic Services), while, on the other hand, according to the commented draft of the law, he is exposed to proceedings before the Freedom of Speech Committee and its arbitrary classification of content as legal or illegal.
Keywords: serwisy społecznościowe; ustrój totalitarny; mowa nienawiści